How might we do it better? Applying educational curriculum theory and practice in talent development environments - Moran, J. J.; Craig, M. P.; Collins, D. (Sports Coaching Review, 2024)
Although Talent Development is a key function for sports organisations, too little work has focused on the establishment of evidence-grounded methods for optimising progress. Drawing principally on the work of Tyler (1949) and Kelly (2009), our aim is to examine constructs from the field of curriculum studies to establish a range of educational concepts and frameworks that would support talent pathway coaches. Using four fundamental questions concerning curriculum design suggested by Tyler (1949) as a frame, i.e. purpose, content, methods or procedures, and evaluation, we present a range of tangible and robust frameworks and ideas that might be applied to talent pathways. Additionally, we have found accordance between several concepts from curriculum theory and practice and existing practices within talent development pathways. Having an awareness of when and where congruency exists would afford practitioners and scholars the opportunity to refine and cultivate more coherent, purposeful and justifiable talent development environments.